A novel mode shape reconstruction method for damage diagnosis of cracked beam. (1st May 2019) - He, Jingjing; Zhou, Yibin
Highlights: A novel output-only damage diagnosis method is proposed. It provides a general methodology for damage diagnosis without knowing the healthy state of targets. The four-order Fourier series fitting method is employed for more accurate baseline data reconstruction. Influences of measurement noise, single damage, multi-damage and broader damage on the proposed method are investigated. Abstract: This paper presents a novel mode shape reconstruction method for damage diagnosis of cracked beam. The proposed method uses output-only data of damaged structure to identify and reconstruct the mode shape of healthy structure. Following that, the curvature mode shapes (CMS) is employed as a damage sensitive feature to locate the damage. In order to identify the mode shape of a target structure with measurement noises, EMD with intermittency criteria is applied to separate dynamic responses into individual modal responses of all grid points on the target structure. A statistical analysis is proposed to evaluate mode shapes from obtained modal responses. Then the Fourier series fitting is employed to mathematically represent the mode shape of the healthy structure. After that, the curvature mode shapes (CMS) which has been investigated as a promising feature for damage identification are acquired by a central difference approximation. Numerical studies are conducted for methodology illustration and validation. Effects of broader damage, multiple damage and measurement noise level are investigated in detail. The accuracy and effectiveness of the proposed method are demonstrated and verified by comparison with conventional method. Finally, a two-span continuous steel I-girder bridge is used to demonstrate the proposed method for more practical applications.